Melanin-Perovskite Composites for Photovoltaics - Paulin, João Vitor (Universidade Estadual Paulista (Unesp), 2026)
This project aims to explore the potential of perovskite solar cells (PSCs) with melanins as organic additives. PSCs represent a promising alternative to silicon solar cells due to their comparable efficiency and lower production cost. However, challenges such as long-term stability and efficiency persist. The goal is to investigate the influence of melanins on the stability, efficiency, and durability of PSCs, by exploring their defect passivation, metal chelation, and moisture resistance properties. The project includes establishing preparation procedures, structural, morphological, and electrical characterization, as well as manufacturing and device analysis. This project aims to contribute to significant advancements in solar energy technology, driving the transition to a renewable and sustainable energy matrix.
Compósitos de Melanina-Perovskita para Células Fotovoltaicas
Keywords: Renewable energy; Melanin; Photovoltaic devices; Perovskite solar cells; Energia renovável; Melanina; Dispositivos fotovoltaicos; Células solares de perovskita